Clinical practice of one-lung ventilation in mainland China: a nationwide questionnaire survey - Hong-jin Liu; Yong Lin; Wang Li; Hai Yang; Wen-yue Kang; Pei-lei Guo; Xiao-hui Guo; Ning-ning Cheng; Jie-chao Tan; Yi-na He; Si-si Chen; Yan Mu; et al. (BMC Anesthesiology)
Abstract Background Limited information is available regarding the application of lung-protective ventilation strategies during one-lung ventilation (OLV) across mainland China. A nationwide questionnaire survey was conducted to investigate this issue in current clinical practice. Methods The survey covered various aspects, including respondent demographics, the establishment and maintenance of OLV, intraoperative monitoring standards, and complications associated with OLV. Results Five hundred forty-three valid responses were collected from all provinces in mainland China. Volume control ventilation mode, 4 to 6 mL per kilogram of predictive body weight, pure oxygen inspiration, and a low-level positive end-expiratory pressure ≤ 5 cm H2O were the most popular ventilation parameters. The most common thresholds of intraoperative respiration monitoring were peripheral oxygen saturation (SpO2) of 90–94%, end-tidal CO2 of 45 to 55 mm Hg, and an airway pressure of 30 to 34 cm H2O. Recruitment maneuvers were traditionally performed by 94% of the respondents. Intraoperative hypoxemia and laryngeal injury were experienced by 75% and 51% of the respondents, respectively. The proportions of anesthesiologists who frequently experienced hypoxemia during OLV were 19%, 24%, and 7% for lung, cardiovascular, and esophageal surgeries, respectively. Up to 32% of respondents were reluctant to perform lung-protective ventilation strategies during OLV. Multiple regression analysis revealed that the volume-control ventilation mode and an SpO2 intervention threshold of < 85% were independent risk factors for hypoxemia during OLV in lung and cardiovascular surgeries. In esophageal surgery, working in a tier 2 hospital and using traditional ventilation strategies were independent risk factors for hypoxemia during OLV. Subgroup analysis revealed no significant difference in intraoperative hypoxemia during OLV between respondents who performed lung-protective ventilation strategies and those who did not. Conclusions Lung-protective ventilation strategies during OLV have been widely accepted in mainland China and are strongly recommended for esophageal surgery, particularly in tier 2 hospitals. Implementing volume control ventilation mode and early management of oxygen desaturation might prevent hypoxemia during OLV.